Some Recommendations for Preventing Child Sexual Abuse in Viet Nam - Phuc Nguyen, Thanh (International Journal of Criminology and Sociology, 2022)
Crime prevention is an outreach measure to stop crime before it can occur. Prevention measures vary in different countries. Child sexual abuse is an issue of growing concern in Viet Nam. Child sexual abuse can cause serious damage to cognitive, social, and emotional development of a child. Effectively combatting this serious form of violence against children requires. Vietnamese government has initiated and supported services and policies that enhance children’s development, health and safety as well as advocated for policies and programs to help meet the basic needs of children and families. In this paper, the author intends to exam the child sexual abuse situation and crime prevention in the world and Vietnam